Secured information sharing in supply chain management: Modified data sanitization with optimal key generation via hybrid algorithm. (November 2022) - Kalyani, Dasari; Srivani, Putta; Pradeep, S
Highlights: Enhances the security and privacy of proposed "block chain assisted supply chain management (SCM)", where the "Modified data sanitization and data Restoration" is carried out with optimal key generation process to preserve the sensitive data in each blocks. Introduces Whale Updated Butterfly Optimization model for generating optimal key that aids in data sanitization and restoration in SCM with block chain technology. Furthermore, the adopted method has accomplished a minimal key sensitivity value of 0.39782 at 10th percentage, whereas, the compared models like FF, PSO, WOA and BOA has acquired relatively minimal values of 0.43363, 0.99961, 0.41525 and 0.87563. Abstract: In the majority of commercial scenarios, supply chain management (SCM) is turning out to be a fundamental focus area. In SCM, a hopeful solution for secured information sharing (IS) is blockchain technology. Nevertheless, it is a bit crucial to maintain security at all levels of blockchain, and therefore private and public-key cryptography is often favored. This study improves the security and privacy of a suggested "blockchain assisted supply chain management (SCM), " in which "Modified Data Sanitization and Data Restoration" is performed with an ideal key generation technique to retain sensitive data in each block. The major challenge that must be overcome to make data transmission security is optimal key selection. Significantly, the proposed hybridized algorithm is used to generate the optimal key in both processes. The proposed hybrid model is known as Whale Updated Butterfly Optimization (WU-BO) and is a conceptual mixture of "Butterfly optimization algorithm (BOA) and Whale Optimization Algorithm (WOA)."Eventually, the examination is performed for verifying the enhancement of the developed model.